THE PRESENT DAY RELEVANCE OF EKPE SOCIETY/MASQUERADE TO THE EFIKS OF NIGERIA - Offiong Offiong Asuquo (Universitas Negeri Makassar, 2020)
The Efiks have a lot of traditional plays and masquerades. Among them are Ekpe, Ukwa, Nnabo, Ibom, Ibo, Abang, Okpo, Ofiom, Tinkoriko and Nnuk among others. The origin of most of them are obscure, but they are all colourful masquerades which often display and entertain at festive and important occasions. Some of them are associated with cults or societies which play important roles in the community. They include Ekpe, Ukwa and Nnabo. This paper examines the meaning of Ekpe play and society, its history and background, its past role in the community, and its relevance and present day role in the society